The Effect of Workload and Work Environment on Employee Performance Through Work Stress as a Mediation Variable at PT Dharma Kyungshin Indonesia - Fitriya Fitriya; Tita Dewi Putri; Sandi Nasrudin Wibowo (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to study how work environment and workload impact employee performance at PT Dharma Kyungshin Indonesia, with work stress as the main mediating variable. The background of this study deviates from the importance of employee performance to support the productivity and competitiveness of the company, especially in the motorized transportation sector, which produces high production pressure. This study was conducted with a quantitative approach and using descriptive methods. A total of 150 employees were used in this study as samples, a total population of 250 employees. Data analysis techniques used validity, reliability, classical assumptions, regression, and mediation tests. This study identified a significant impact of workload and work environment on work stress. Workload has a large negative impact on employee performance, but the work environment has a large positive effect. However, work stress has a large impact on performance. Work stress does not significantly communicate the relationship between workload and performance. The relationship between work environment and performance can be communicated significantly. In short, company management must pay attention to the distribution of workload and create a supportive work environment to manage work stress and develop employee performance. This study provides theoretical contributions to the development of personnel management and is a practical reference for companies in designing strategies to improve employee services.